Pengaruh Pertumbuhan Belanja, Pendapatan Asli Daerah, Ukuran Legislatif, dan Dana Perimbangan Terhadap Kinerja Keuangan Pemerintah Daerah - Indrani Nuzul Fauziyah; Diah Ekaningtias (Program Studi Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
Local government financial performance is the achievement of policies drawn up over a certain period, measured by the financial system in accordance with the law. The purpose of the study was to determine and understand the effect of spending growth, local revenue, legislative measures, and balancing funds on the financial performance of local governments in East Java Province as measured by the effectiveness and efficiency of revenue and expenditure budget absorption. The sample of this research is districts and cities in East Java Province during the 2015- 2019 period. Statistical analysis techniques are multiple linear regression and saturated sampling method. The results showed that the growth of spending, local revenue, legislative size, had no effect on the financial performance of local governments by measuring the effectiveness of the absorption of the revenue budget, while the balancing fund had an effect on the financial performance of local governments by measuring the effectiveness of the absorption of the revenue budget. The results of the research on spending growth affect the financial performance of local governments using efficient measurements, while local revenue, legislative measures, and balancing funds do not affect the financial performance of local governments using efficient measurements.